Cardiac Mitochondrial Calcium Loading Capacity Is Severely Affected after Chronic Cholestasis in Wistar Rats. (1st March 2003) - Oliveira, Paulo J.; Rolo, Anabela P.; Seiça, Raquel; Santos, Maria S.; Palmeira, Carlos M.; Moreno, António J.M.
Abstract : Background: Cardiovascular changes correlated with some forms of hepatic disease are being reported in the literature. Objectives: The aim of this work was to characterize cardiac mitochondrial bioenergetics and calcium buffering capacity in Wistar rats injected with six weekly doses of α-naphthylisothio-cyanate (ANIT), a compound known to induce cholestasis in animal models. Methods: Isolated heart mitochondria were obtained from both injected and control animals and bioenergetic parameters were measured, as well as the capacity to buffer externally added calcium and the mitochondrial content of reduced protein thiol groups. Blood biochemistry analyses were obtained at the initial and end points of treatment. The in vitro ANIT effect on isolated heart mitochondria was also studied. Results and Discussion: Our results showed that the respiratory control ratio was the only parameter affected in injected animals ( p < .05, n = 5). Nevertheless, heart mitochondria from injected animals showed an inability to accumulate added calcium owing to an increased susceptibility to the calcium-dependent mitochondrial permeability transition ( p < .0001, n = 5). The effects were still present 1 week after ending ANIT administration, when serum markers for liver injury and hyperbilirubinemia were already abated (although in the presence of bile duct proliferation). To our knowl- edge, this is the first time that cardiac mitochondrial calcium homeostasis and mitochondrial respiratory ratio are seen affected during ANIT-induced cholestasis, prevailing even in the absence of hepatic damage serum markers.